EVALUATION OF FUNCTIONAL OUTCOMES FOLLOWING OPEN REDUCTION AND INTERNAL FIXATION IN RADIAL HEAD AND NECK FRACTURES (Journal of Medical & Health Sciences Review, 2025)
ABSTRACTObjective: This study aimed to evaluate the early functional recovery following Open Reduction and Internal Fixation (ORIF) of radial head and neck fractures using the Mayo Elbow Performance Score (MEPS).Design: A Quasi-experimental study.Place and Duration: It was conducted at the Orthopaedic Department, Jinnah Hospital Lahore, from September 2024 to March 2025.Methodology: Ninety-five patients aged 18–75 years with closed Mason Type III or IV radial head/neck fractures were enrolled. Surgical exposure was achieved via posterolateral(Kocher) or straight lateral approaches, and fixation utilized K-wires, screws, or plates. MEPS was recorded at 6 weeks and 3 months post-operatively. Data analysis was performed using SPSS 24.0, with comparisons made using t-tests, Mann-Whitney U, and Chi-square tests.Results: Out of 105 initially enrolled patients, data from 95 were analysed. The majority (80%) had Mason Type III fractures; 47.4% had combined radial head and neck fractures. At 6 weeks, 76.84% reported no to mild pain, but only 33.68% regained full range of motion, and 73.68% experienced limitations in daily activities. By 3 months, outcomes significantly improved: 97.89% reported no/mild pain, 77.89% regained full motion, 89.47% had stable elbows, and only 20% had persistent functional limitations.The mean MEPS score at 6 weeks was 70.99 for Mason Type III and 60.79 for Type IV(p = 0.030). At 3 months, Type III patients had a mean score of 94.01, while Type IV had 82.63(p < 0.001), indicating significantly better outcomes in less complex fractures. Gender was significantly associated with better MEPS scores at both follow-ups, favouring males(p < 0.05). Other variables, including time to surgery and fracture type, did not show a significant effect on final functional outcomes.Conclusion: ORIF significantly improves function in radial head/neck fractures, especially Mason Type III. Gender influenced recovery, while early intervention timing showed no statistical impact.